Physico-chemical characterization and in vitro biological study of manganese doped β-tricalcium phosphate-based ceramics for bone regeneration applications - GÜNDÜZ, OĞUZHAN (My University, 2023)
This work evaluates the effects of manganese (Mn) doping on the morpho-structural features, mechanical performance, and in vitro biological response of beta-tricalcium phosphate (β-TCP) derived bioceramics for bone tissue engineering applications. Five different Mn doping levels (i.e., 0.01%, 0.05%, 0.1%, 0.5%, and 1 wt.%) were investigated, with the β-TCP-based bioceramics being sintered at four temperatures (i.e., 1000, 1100, 1200, and 1300 °C). A densification improvement was induced when using Mn in excess of 0.05 wt.%; the densification remained stationary in the sintering temperature range of 1200 − 1300 °C. The structural analyses evidenced that all samples sintered at 1000 and 1100 °C were composed of β-TCP as major phase and hydroxyapatite (HA) as a minor constituent (~ 4–6 wt.%). At the higher temperatures (1200 and 1300 °C), the formation of α-TCP was signalled at the expense of both β-TCP and HA. The Mn doping was evidenced by lattice parameters changes. The evolution of the phase weights is linked to a complex inter-play between the capacity of the compounds to incorporate Mn and the thermal decomposition kinetics. The Mn doping induced a reduction in the mechanical performance (in terms of compressive strength, Vickers hardness and elastic modulus) of the β-TCP-based ceramics. The metabolic activity and viability of osteoblastic cells (MC3T3-E1) for the ceramics were studied in both powder and compacted pellet form. Ceramics with Mn doping levels lower than 0.1 wt.% yielded a more favorable microenvironment for the osteoblast cells with respect to the undoped β-TCP. No cytotoxic effects were recorded up to 21 days. The Mn-doped β-TCPs showed a significant increase (p < 0.01) in alkaline phosphatase activity with respect to pure β-TCP.
Keywords: Mühendislik ve Teknoloji; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Malzeme Bilimi; MALZEME BİLİMİ, SERAMİK; MALZEME BİLİMİ, ÇOKDİSİPLİNLİ; Engineering, Computing & Technology (ENG); MATERIALS SCIENCE; MATERIALS SCIENCE, CERAMICS; MATERIALS SCIENCE, MULTIDISCIPLINARY; Seramik ve Kompozitler; Fizik Bilimleri; Malzeme Kimyası; Ceramics and Composites; Physical Sciences; Materials Chemistry; Cytocompatibility; Manganese doping; Physical–chemical properties; Rietveld XRD analysis; β-tricalcium phosphate; Manganese doping; β-tricalcium phosphate; Physical–chemical properties; Rietveld XRD analysis; Cytocompatibility